Organizational conflict management strategies and their impact on the job performance / rashad hospital applied research training program - كاظم فايق جواد; راشد علي رحمه (Journal of Economics and Administrative Sciences, 2018)
This research aims to study to the strategic management of organizational conflict, which included (concept of conflict and development, types Altzimi conflict, ,management strategies organizational conflict) and its impact on job performance, which included( the concept of performance, elements functionality,) As well as the impact of the conflict on job performance has been selected Rashad training Hospital affiliated to the Department of Health in Baghdad’s Rusafa, as the most important service hospitals with the exact specialty in psychiatry and its impact on the lives of citizens and how to enable the hospital aware of the strategic management of organizational conflict raises the level of functionality provided and make them an incentive to raise the spirit of competition and creativity among nurses, which increases the effectiveness of the hospital to provide the best health care. The sample of (100) nurses. The study was exploratory and the resolution is the means to gather information adopted by the researcher, which, as well as experience through his work at Al-Rashad Training Hospital for several years, was to include the subject of research, inter intellectual questions that have evolved collectively research problem, and then determine its objectives and its importance, as well as the formulation of hypotheses search. It was the use of a lot of statistical methods, such as (arithmetic mean, standard deviation, percentages, correlation coefficient, simple) Regression to measure the level of research and diagnostic variables coefficient, and the correlation coefficient ranks (Berson) to measure the nature of the influence relations, the coefficient of linear regression Simple (Simple linear regression ) to measure the correlation, found this research to a set of conclusions was the most important (Odarhospy Rashad training used most often the task force and control, there is the impact of strategies for organizational conflict management functionality) Researcher presented a set of recommendations, most notably (the hospital administration alleviate used to after the task force, control and diversifying their strategies to the process of managing organizational conflict) For the purpose of deepening the studies and research in contemporary management fields and strategic management study suggests the need for a number of studies and future research